Experimental investigation of parallel type evacuated tube solar collector using nanofluids - Sasikumar, Subramaniam Babu; Santhanam, Harikrishnan; M. M., Noor; Devasenan, Madhesh; Hafiz, Muhammad Ali (Taylor & Francis, 2020)
The utilization of fossil fuels can be minimized by the application of solar energy. In this paper, the performance of Parallel-Type (PT) Evacuated Tube Solar Collectors (ETSC) using Al2O3 nanofluid was experimentally investigated. The solar collector was used during both the on-peak and off-peak periods. As a result, the efficiency of the ETSC was calculated by adding various range of particle concentration of Al2O3 nanoparticles in the base fluid. The circulating fluid with flow rates of 0.035 and 0.065 kg/sec. The maximum efficiency procured as of the solar collector at a flow rate 0.035 kg/sec with concentrations of 0.1, 0.2, and 0.3 vol% of Al2O3 nanofluid was 61.8%, 65.4%, and 69.5%, respectively. An improvement of 6.7%, 7%, and 7.7%, efficiency was achieved compared to the flow rate of 0.065 kg/sec. The most optimal concentration of 0.3vol% Al2O3 nanofluid shown progress in thermal efficiency compared to other percentage of nanofluid and water. Improvisation of efficiency by incorporating the Al2O3 nanoparticles in the base fluid in the evacuated tube solar collector. Withal, the investigation includes the prognostication of temperature at entry and exit fluid, solar radiation, ambient temperature, energy output, and also the collector efficiency. Moreover, the investigation was focused toward the evaluation of the efficiency in PT-ETSC at various condition of the environment. Finally, based on the test results, present work could be recommended for agriculatural purpose specifically in vegitable drying conditions.